Organisasi dan Komunitas Klub Poligami di Indonesia: Membangun atau Membangkang Persepsi Masyarakat? - Qosim, Ilhamuddin; Gunawan, Sahrul (Prodi Ahwal Asy Syahsiyah, Fakultas Syariah dan Hukum, Universitas PTIQ Jakarta, 2024)
This study examines the role of polygamy organizations and clubs in Indonesia, such as Forum Poligami Indonesia (FP Indonesia), Sakinah Group (PSG), and the Polygamy Club of Indonesia, in shaping public perceptions of polygamy. The study focuses on these organizations' efforts to present a positive narrative of polygamy as a legitimate part of Islamic law, as well as the challenges they face from cultural resistance, media, and gender inequality. Through qualitative methods, in-depth interviews, and observation, it was found that while polygamy organizations provide moral and spiritual support to their members, they struggle to change the broader public's negative perception. External factors such as media, culture, and strict regulations contribute to public resistance to polygamy. This research offers a deeper understanding of the dynamics of polygamy organizations in Indonesia and their role in shaping public perceptions.